The Guidelines for Human Capital Development in the Industrial Businesses Sector to Enhance Competitiveness - Numfon Senangkanikorn; Taweesak Roopsing; Thanin Silpcharu (Migration Letters, 2023)
The development of human capital in the industrial business sector promotes entrepreneurs to enhance their competitiveness and contribute to sustainable economic growth. The study’s objective is to investigate the guidelines for human capital development in the industrial business sector to enhance competitiveness and develop a structural equation model. Qualitative research was conducted through in-depth interviews and group discussions. Quantitative research was conducted through a survey of 500 entrepreneurs. This research utilized descriptive, inferential, and multivariate statistics.The research findings regarding the guidelines for human capital development in the industrial business sector with the highest average importance were ranked as follows: Organizational Change (X̄= 4.13, S.D. = 0.45), Knowledge Management (X̄ = 4.13, S.D. = 0.47), Technology Management (X̄ = 4.13, S.D. = 0.50), and Monitoring and Evaluation (X̄ = 4.12). The hypothesis testing results indicated that medium-sized and large organizations do not differ significantly in terms of their importance strategies.